Psychological Safety in High-Performance Sport: Contextually Applicable? - Taylor, Jamie; Collins, Dave; Ashford, Michael (Frontiers in Sports and Active Living, 2022)
High-performance sport has been subject to a number of ‘fads’ in recent years. Of late, there has been a rising interest in psychological safety, a construct with a strong empirical basis in the business context. As research and practice interest grows in psychological safety, there are early indications of practitioners and, to a lesser extent research, treating the construct as being universally transferable. We offer three central concerns with this situation. Firstly, it seems that a variety of different interpretations in use may limit practical application of the construct. Secondly, a concern that not all dimensions of psychological safety are transferable or applicable in the high-performance sport context, especially for athletes. Finally, emerging evidence from outside of sport suggesting potential downsides to the perceptions of psychological safety in a performance/selection setting. We suggest, that as with all theories and constructs, there is a pressing need for nuance and context-specific evidence in how researchers and practitioners approach transferability plus, perhaps, a little more understanding of the real-world high-performance context.